ANALYSIS OF VIOLENCE IN CITY OF GOD FILM DIRECTED BY FERNANDO MEIRELLES - Simanjuntak, Marudut Bernadtua; Barus, Irma Rasita Gloria; Resmayasari, Ira (JOURNAL OF ADVANCED ENGLISH STUDIES, 2021)
Fernando Meireles' "City of God" is one of the most highly regarded crime films in the early 2000s. The criminal genre, especially in this film, shows many scenes of violence against children, women, and the community around Rio de Jeneiro. The violent scene continues from the beginning to the end of the film. The purpose of this research is that the writer wants to analyze the violence contained in the film City of God, both physical and psychological violence. This research uses the descriptive quantitative content analysis method which aims to study and analyze communication and movie scenes systematically and objectively to the messages seen. The results of this study indicate that the film City of God shows quite massive scenes of physical and psychological violence against fellow gangsters, drug dealers, minors, innocent families, and even harassment in the form of rape against women. The conclusion from the analysis of this research is the need for several elements of society to be involved in studying film, sensitivity to violence, and the need for age restrictions in watching certain films, including the film City of God.